Government Policy on Covid-19 : Perspective of Certain Professions in Indonesia - Dyah Indraswati; Uwi Martayadi; Sovia Rahmaniah; Mohammad Archi Maulyda; Prihma Sinta Utami (Jurnal Kebijakan Kesehatan Indonesia, 2021)
On December 2019, Wuhan, the capital city of Hubei, China, became the center of a pneumonia outbreak that indicated the discovery of a new type of Coronavirus named Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) which caused Covid-19. The type of this research was descriptive qualitative. Data collection procedures were done by literature study, interviews, and documentation. The subject of the study was 16 people with different professions. Some professions which came in contact with Covid-19 and the policies include healthcare professionals, online transportation drivers, sellers, teachers/lecturers, and journalists. To analyze the data, the researcher used data reduction, data presentation, and drawing conclusions. This study aimed to examine government policy and observe the perspectives of Indonesian people from different professions about the Covid-19 virus outbreak and its impact on socio-economic life. The results of the study showed that Indonesian government's policies were appropriate in overcoming the Covid-19 virus outbreak even though the benefits were not evenly distributed for the entire community.